Techno-economic analysis of micro-algae bio-jet fuel production processes - Ewurum, Chioma Eberechukwu (2019)
The production of bio-fuel from autotrophic micro-algae are being extensively studied and documented. However very few focuses specifically on the production of bio-jet fuel, with even fewer that assesses both the environmental and economic state of micro-algal bio-jet fuel production through modelling efforts.